I am the Dark Mirror the vampire of my own heart' : the postmodern vampire in fiction, film and culture 1975-2008 - Ní Fhlainn, Sorcha (Trinity College (Dublin, Ireland). School of English, 2009)
This thesis explores the distinct shift of the vampire, in film, fiction and culture, from 1975 - 2008. Each chapter of this thesis represents four ‘cultural decades’ of change, through which we see the development of the Postmodern Vampire from a monstrous ‘other’ at the margins of the story to the central narrator in his own tale. This transition is highly significant as it recognises a shift from Modernity to Postmodernity, and removes the previously established hierarchal structure of culture in favour of academically critiquing all modes of popular culture and representation. Vampires inhabit all facets of popular culture and narrate their place within our culture through these streams of representation. It is the objective of the thesis to locate specific dialogues on politics, economics, sexualities, and religious views within the vampire narrative in popular culture and cultural history, from Fred Saberhagen’s novel The Dracula Tape in 1975 to Stephenie Meyer’s popular adolescent novels, the Twilight series; the most recent instalment published in 2008.
Embargo End Date: 2022-01-01
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin, 2009